"Do the Hard Work": Identity Development and First Year Doctoral Students - Davin J Carr-Chellman; Carol Rogers Shaw (Adult Education Research Conference, 2017)
This qualitative, phenomenological study examined the experiences of first year graduate students learning to become doctoral students in education doctoral programs. Findings include the centrality of identity development and social justice.
Keywords: doctoral study; phenomenology; identity; social justice